Multi-Omics Analysis of the Immune Effect of the Engineered Exosome Drug Delivery System in Inducing Macrophage Apoptosis - Wei Xiang; Zhoujun Zhu; Qisong Shang; Parhat Yasin; Yuanyuan Wu; Xinghua Song (Pharmaceutics)
Background: In this study, exosomes were engineered with anti-CD47 antibody and loaded with rifapentine to improve their ability to target macrophages for drug delivery. Methods: Exosomes from RAW264.7 cell supernatant were extracted by differential centrifugation, antibody-modified, and drug-loaded ultrasonically. After co-culturing with macrophages, transcriptomics and proteomics screened differentially expressed genes and proteins. Western Blot identified macrophage polarization, ELISA detected inflammatory indicators, and an apoptosis kit was used for fluorescence staining. Results: Transcriptome sequencing showed that 406 genes in the macrophages changed significantly, with pathways like TNF and NF-κB. Proteomics identified 7478 proteins, 433 with significant differences. Western Blot indicated M1 polarization. Fluorescence staining showed apoptosis in the antiMExo-RIF group. Conclusions: The study provides multi-omics evidence of the immune mechanism of the engineered exosome drug delivery system in inducing macrophage apoptosis, revealing potential molecular mechanisms and the great potential use of engineered exosomes in treating macrophage-related diseases.